Analisis Fasilitas Kerja Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan Di Hotel Le Meridien Jakarta - Efanandosa, Efanandosa; Iskandar, Hari (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study aims to analyze the influence of workplace facilities and leadership styles on employee performance at Hotel Le Meridien Jakarta. It was found that well-equipped, tailored, and user-friendly workplace facilities enhance employee comfort and efficiency. Meanwhile, supportive, participative, and achievement-oriented leadership motivates employees towards high goal achievement. Based on the research findings, it is recommended to enhance employee welfare through comprehensive welfare programs, implement effective leadership styles, improve or add adequate workplace facilities, and organize relevant training and development. The study restricts issues to workplace facilities and leadership styles as intervening variables. It was found that workplace facilities and leadership styles significantly influence employee performance at Hotel Le Meridien Jakarta. Through these efforts, the hotel can attain competitive advantages in the hospitality industry, enhance guest and employee satisfaction. The conclusion is supported by an analysis of guest satisfaction survey data and research observations on workplace facilities and leadership styles at Hotel Le Meridien Jakarta. Suggestions include improving employee welfare, implementing effective leadership styles, upgrading workplace facilities, and organizing relevant training and development. Thus, the hotel can enhance employee performance, achieve higher guest satisfaction, and strengthen its position in the hospitality market.